Repeated intravesical injections of platelet-rich plasma improve symptoms and alter urinary functional proteins in patients with refractory interstitial cystitis - Jiang, Yuan-Hong; Kuo, Yuh-Chen; Jhang, Jia-Fong; Lee, Cheng-Ling; Hsu, Yung-Hsiang; Ho, Han-Chen; Kuo, Hann-Chorng (Scientific reports, 2020)
Repeated intravesical injections of autologous platelet-rich plasma (PRP) have been shown to improve symptoms in patients with interstitial cystitis/bladder pain syndrome (IC/BPS); however, there is a paucity of objective evidence of the effectiveness of this therapy. In this study, we investigated the changes in urinary markers after PRP treatment. Forty patients with IC/BPS who were refractory to conventional therapy received four injections of PRP at monthly intervals; 10 mL PRP solution with 2.5 times the peripheral blood platelet concentration was used. Urine levels of thirteen functional proteins, growth factors, and cytokines were assessed at baseline and at the 4th PRP injection. The clinical parameters included visual analog scale (VAS) pain score, daily urinary frequency, nocturia episodes, functional bladder capacity, and global response assessment (GRA). The GRA and symptom score significantly decreased post-treatment. In patients with GRA ≥ 2, the success rates at 1 month and at 3 months after the 4th PRP injection were 70.6% and 76.7%, respectively. The VAS pain score, frequency, and nocturia showed a significant decrease (all p < 0.05). Urinary levels of nerve growth factor, matrix metalloproteinase-13, and vascular endothelial growth factor significantly decreased post-treatment ( p = 0.043, p = 0.02, and p = 0.000, respectively); platelet-derived growth factor-AB showed a significant increase ( p = 0.004) at the 4th PRP treatment compared with baseline. In this study, repeated intravesical PRP injections provided significant symptom improvement in IC/BPS patients with concomitant changes in the related biomarker levels. Trial registration: ClinicalTrial.gov: NCT03104361; IRB: TCGH 105-48-A.